WISDOM APPRECIATION IN SUSTAINABLE MANAGEMENT THOUGHT: AS GROUNDED THEORY - Nuringsih, Kartika; Budiono, Herlina; Maupa, Haris; Taba, Muhammad Idrus (International Journal of Application on Economics and Business, 2023)
Along with human civilization, the function of business management has changed. Adaptation is carried out as a form of wisdom in understanding social and environmental issues for becoming a new pillar in building business management sustainability. The qualitative study with a grounded theory approach is carried out to appreciate the thought of wisdom in developing management philosophy and using desk study to analyze data from scientific publications. The result proves that the existence of business management has evolved over the past 100 years from classical, neo-classical, and modern management, even in the era of sustainability. Starting from the industrial revolution 1.0 with the achievement of production efficiency up to 4.0 with speeding of information technology. Although different challenges in each era, the management goal remains the same to manage limited resources in order to meet the various desires of a changing world. Aligning with environmental issues, harmony among social responsibility, and economic growth is needed as the foundation of management philosophy so that a sense of wisdom characterizes the sustainability of current and future business goals. This study serves as a grounded theory to trace the essence of wisdom along the course of classical to modern management thinking that is synergized with sustainable development.